Public Health and Economic Consequences of Vaccine Hesitancy for Measles in the United States. (4th October 2017) - Lo, Nathan C; Hotez, Peter J
Abstract: Background: Routine childhood vaccination is declining in some regions of United States due to vaccine hesitancy, which risks the resurgence of many infectious diseases with public health and economic consequences. There are ongoing policy debates on the state and national level, including legislation around non-medical (e.g., personal belief) exemptions for childhood vaccination and possibly a special government commission on vaccine safety, which may affect vaccine coverage. Methods: Using the case example of measles-mumps-rubella (MMR) vaccination and measles, we estimated the number of measles cases in U.S. children (ages 2–11 years) and the associated economic costs under scenarios of different levels of vaccine hesitancy. We used publicly available data from the U.S. Centers for Disease Control and Prevention to simulate county-level MMR vaccination coverage. We adapted a stochastic mathematical model for infectious disease transmission that estimated a distribution for outbreak size as it relates to vaccine coverage. We sourced economic costs per measles case from literature. We tested the effect of increasing the prevalence of vaccine hesitancy and also the removal of non-medical exemptions. We calibrated the model to annual measles cases in U.S. children over recent years, and validated the model prediction using an independent dataset from England and Wales. Results: We estimated that a modest 5% decline in MMR vaccine coverage in the United States would result in a 3-fold increase in measles cases for children ages 2–11 nationally every year (Figure 1), with an additional US 2.1 million in public sector costs. The numbers would be substantially higher if unvaccinated infants, adolescents, and adult populations were also considered. There was variation around these estimates due to the stochastic elements of measles importation and sensitivity of some model inputs, although the trend was robust. Conclusion: This analysis predicts that even minor reductions in childhood vaccination, driven by vaccine hesitancy, will have substantial public health and economic consequences. The results support an urgent need to address vaccine hesitancy in policy dialogues at state and national level, with consideration of removing personal belief exemptions of childhood vaccination. Disclosures: All authors: No reported disclosures.